Confluent and reticulated papillomatosis: clinical and histopathological study of 10 cases from Lebanon. (3rd November 2011) - Tamraz, H.; Raffoul, M.; Kurban, M.; Kibbi, A.‐G.; Abbas, O.
Abstract Background Confluent and reticulate papillomatosis (CRP) is a rare disorder that has mostly been described in case reports and limited case series. Studies on this condition from our region are lacking. Objective/methods To describe the clinical and histopathological findings, as well as response to treatment of all patients diagnosed with CRP at the American University of Beirut Medical Center (AUB‐MC) between 1999 and 2009, and to compare our findings with those published in the literature. Results Confluent and reticulate papillomatosis was diagnosed in 10 patients (five men, five women). Mean age at diagnosis was 19 years. Duration of lesions ranged from few months to several years. Skin lesions mainly consisted of reticulated, pigmented macules, patches and plaques. The most common area of involvement was the chest in five cases. The rash was asymptomatic in eight patients. Skin biopsy specimens from all patients revealed hyperkeratosis, papillomatosis and variable acanthosis. Whereas follicular plugging was observed in nine cases, anastomosis of the rete ridges was noted in three. Periodic acid Schiff stains highlighted yeast forms in six cases. Conclusion The clinical and histopathological features of the CRP patients in our study are generally comparable to those published in the literature, with minor differences. Clinically, one case had an atypical clinical presentation, and microscopically follicular plugging was seen in the majority of cases. Yeast‐like spores were seen in six cases further supporting a role of Malassezia furfur in the pathogenesis of CRP.